Influence of coplanar double fissures on failure characteristics of sandstone and fracture mechanics analysis - Zhang, Dechao; She, Haicheng; Xiao, Taoli (Frontiers in Earth Science, 2023)
The influence of fissure angles and bridge lengths on rock mechanical properties and failure was analyzed using the uniaxial compression test and the Digital Image Correlation (DIC) technique. The research findings are as follows: 1) Peak stress and elastic modulus of the samples exhibited an obvious change trend with the change in fissure angle. The fissure angle has a more significant effect on a rock’s mechanical properties than the length of the rock bridge. 2) With an increase in the fissure angle, the number of surface cracks, main failure cracks and surface spalling decreased, whereas the area of the falling blocks significantly increased. However, with an increase in bridge length, the characteristics of crack propagation and spalling are essentially the same. During crack propagation, the connection of the rock bridge is related to its fissure angle and length. 3) At a low fissure angle, the failure mode of rock samples is dominated by tensile-failure cracks; with an increase in fissure angle, the tension-damage to shear-damage crack transformation will form a mixed tensile-shear damage mode; at the same time, with an increase in bridge length, the rock bridge becomes more difficult to connect, and the local crack expansion failure changes from tensile-shear cracks to tensile cracks. 4) Stress on the coplanar double-fissured rock sample was simplified and analyzed to explain the behavior of fractures on the sample. These research results have an important guiding value for engineering optimal designs.